Peningkatan Harga Diri pada Remaja dengan Tuberkulosis Kelenjar melalui Terapi Ners Generalis - Fatrichia Nur Rahma; Yossie Susanti Eka Putrii; Ice Yulia Wardhani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to provide generalist nurse intervention to adolescent clients with situational low self-esteem. The method used was a case study approach with one respondent, carried out for two days on 1-2 April 2021. The results obtained were that generalist therapy was proven to increase adolescent self-esteem. Generalist therapy has proven effective with specialist nursing therapy, including supportive therapy and family psychoeducation. Keywords: Situational low self-esteem, Adolescents, Glandular TB, Generalist Nurse Therapy